Authenticity and originarity in foreign language learning in the diaspora - Mühr, Stephan (Stellenbosch Papers in Linguistics Plus, 2012)
This paper reflects on a telecollaborative project with second-year students of German between theUniversity of Pretoria (South Africa) and Colgate University (United States of America) in 2008. Theproject resulted from a critical discussion on the potential of online technology in foreign languagelearning (FLL). A central concern in implementing such technology should be the all-inclusive,authentic use of all language faculties, which Peeters (2008) calls "originarity". The latter overcomesstructuralist or poststructuralist reductions of language as a medium of communication. Thus, theessence of FLL can be redefined, not as the acquisition of mimicry of specific codes, but asintercultural dialogue.Keywords : originarity, authenticity, foreign language learning, video conferencing